Pengaruh model pembelajaran discovery learning terhadap pemahaman siswa pada mata pelajaran geografi - Marshanda, Umi Fadhila; Sumarmi, Sumarmi (Universitas Negeri Malang, 2023)
One of the issues in teaching is the lack of student understanding. This investigation seeks to ascertain whether the Discovery Learning approach to learning has an effect on the comprehension of social studies students in class XI at SMAN 9 Malang City. Using a posttest-only group design, a quasi-experimental approach was used in this investigation. The experimental class was chosen, and the control class was chosen using a purposive sampling technique. In this study, various methods of data analysis were employed, including reliability tests, normality tests, validity tests, and non- parametric tests. The treatment given to the Discovery Learning learning model appears to have an impact on students' comprehension of the environmental impact analysis content, according to research findings. Drawing conclusions from the research results based on descriptive analysis calculations where the average control class is 70.14 while the experimental class has an average of 79.75. In addition, the results of the non-parametric test are also the reason for making a decision which Asymp. Sig value. (2-tailed) is 0.000 less than 0.05, it can be concluded that the research hypothesis is accepted. Salah satu masalah dalam pengajaran adalah kurangnya pemahaman siswa. Penelitian ini berusaha untuk memastikan apakah pendekatan pembelajaran Discovery Learning berpengaruh untuk membantu pemahaman siswa kelas XI IPS SMAN 9 Kota Malang. Penelitian ini menggunakan desain penelitian berupa posttest-only group design dengan metode quasi experiment. Kelas eksperimen dipilih, dan kelas kontrol dipilih dengan menggunakan teknik purposive sampling. Dalam penelitian ini digunakan berbagai metode analisis data, antara lain uji validitas, uji reliabilitas, uji normalitas, dan uji nonparametric. Hasil dari pengolahan data, mengatakan bahwa pemahaman siswa terhadap materi analisis mengenai dampak lingkungan dipengaruhi oleh penerapan model pembelajaran Discovery Learning di kelas eksperimen. Pengambilan kesimpulan dari hasil penelitian berdasarkan perhitungan analisis deskriptif dimana rata-rata kelas kontrol 70,14 serta kelas eksperimen memiliki rata-rata 79,75. Selain itu hasil dari uji non-parametrik juga menjadi alasan dari pengambilan keputusan yang mana nilai Asymp. Sig. (2-tailed) bernilai 0,000 lebih kecil dari 0,05, maka dapat disimpulkan hipotesis penelitian diterima.